FINANCIAL KNOWLEDGE, FINANCIAL WELLBEING, AND ONLINE SHOPPING ADDICTION AMONG YOUNG INDONESIANS - Sherly Tanoto; Evelyn Evelyn (Jurnal Manajemen dan Kewirausahaan, 2019)
With the recent booming of e–commerce business in Indonesia, it is essential to conduct further studies on online shopping behavior of Indonesians. Past studies on online shopping addiction emphasize only psychological factors and overlook financial factors. To fill this research gap, this study aims to examine the association and effect of financial knowledge and financial wellbeing on online shopping addiction. The Bergen Shopping Addiction Scale (BSAS) was adopted to assess online shopping addiction whilst financial knowledge and financial wellbeing scales from Australian Unity were used to measure the other two research variables. Data was collected through an online survey of 230 young Indonesians. To analyze the data, Pearson correlation and multiple regression techniques were implemented. Outcomes of this study revealed that most respondents had medium and high levels of financial knowledge and financial wellbeing. Interestingly, addictive respondents showed high financial knowledge and financial wellbeing. Financial knowledge and financial wellbeing were positively related to online shopping addiction. Financial wellbeing was a better predictor because it might be possible that individuals with positive feelings on their financial conditions were more comfortable in increasing their online spending behavior. The results of this study provide insights for future studies and e–commerce owners.Keywords: Online shopping addiction, financial knowledge, financial wellbeing.